Peer Pressure: The Puzzle of Tax Compliance in the Early Nineteenth-Century Russia - Elena Korchmina (European Historical Economics Society (EHES), 2018)
How can developing countries successfully implement income taxes, which are generally desirable but costly to collect? This paper analyses the income tax compliance of elites in a developing country with a low administrative capacity, drawing attention to the role of either voluntary or quasi-voluntary components of tax acquiescence. In 1812, the Russian government introduced the progressive income tax, with the highest tax rate of 10 per cent. After Britain, the Russian Empire became the second country to adopt this levy – under the threat of Napoleonic invasion. Unlike the widely known and deeply investigated British case, the history of Russian income tax suffers from a lack of detailed research. I use a self-compiled unique dataset for estimating the level of tax compliance of the Russian noble elite at the individual level. The dataset is based on the self-reported tax returns of approximately 4,000 Russian aristocrats who had real estate in the Moscow region. Using narrative sources and crosschecking with official bank documents, I reveal not only that the Russian nobility declared reliable income information but also that the share of aristocratic evaders was relatively low (from 30 to 10 per cent). I argue that this surprisingly high level of tax compliance was achieved through a unique mechanism of tax collection involving the channels of social sanctioning and group identity, boosted by the national threat of Napoleonic invasion. This case could be considered as extremely important, insofar as the state could not achieve its fiscal aims due to coercive tools in the hands of bureaucracy but had to rely on subjects' goodwill.
Keywords: H2; N93; N33; 330; Russia; income tax; elite; nineteenth-century